MENUJU DESA MANDIRI: MEWUJUDKAN POTENSI KAMPUNG MELALUI PEMBENTUKAN BUMK - Syahruddin; Beatus Tambaip; Alexander Phuk Tjilen; Paul Adryani Moento; Pulung Riyanto (Yayasan Nusantara Hasana Berdikari, 2023)
The purpose of this service is to make Zenegei village an independent village based on the formation of village-owned enterprises (BUMK). The method used is the Approach Method offered to solve partner problems that have been mutually agreed upon by holding outreach, lectures, discussions, and questions and answers, forming BUMK and training (workshops) for partners. The step to evaluate the implementation and sustainability of the program in the field after the activities are carried out is for the implementing team to evaluate the competence of the community to find out how far the knowledge provided during the training can help partners improve competence in solving problems. The steps taken are by distributing questionnaires to partners to get feedback from partners, as material for evaluating the implementation of sustainable activities. The results of this community service activity are to have an impact on the formation of Village-Owned Enterprises in Zenegi Village in accordance with the Village Law which mandates villages to be able to manage their regional potential so that they can become independent villages. The establishment of Village-Owned Enterprises (BUMK) and training and increasing understanding of the village community in its management in Zenegi Village, which is a partner, is a solution as an effort to develop the local potential of village communities towards an Independent Village.